Crowding-In Capital : How Insurance Companies Can Expand Access to Finance - Karlin, Arthur; Marshall, Euan; Afroz, Mahfuza; Kurdyla, Michael (International Finance Corporation, Washington, DC, 2018)
Development institutions, governments, and the investment community have been exploring ways to increase private capital flows to support critical development projects in emerging markets. A new financing mechanism applies the risk-bearing capacity and know-how of insurance companies to allow these companies to take what are, in many cases, their first insurance exposure to markets and counterparties. This innovative credit insurance solution, called as credit mobilization, is being pioneered to provide long-term funding to developing country banks, and may offer significant potential for scale-up and replication.